TURNING HOBBIES INTO UNIVERSITY SUBJECTS - Musurmonkulova Indira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The integration of hobbies into academic curricula presents an innovative approach to education, allowing students to pursue their passions while gaining formal recognition for their skills and interests. This concept involves transforming personal interests, such as photography, cooking, gaming, or creative writing, into structured university courses or degree programs. By offering dedicated subjects based on hobbies, universities can foster greater student engagement and motivation. Students often show enhanced enthusiasm and commitment when studying topics they are passionate about, leading to deeper learning experiences and improved academic performance. Furthermore, these subjects can encourage interdisciplinary learning, combining elements from various fields such as art, technology, psychology, and sociology. Additionally, turning hobbies into university subjects recognizes the diverse skill sets and experiences that students bring to higher education. It promotes a more inclusive curriculum that values creativity and personal development alongside traditional academic subjects. This approach not only prepares students for the job market by equipping them with practical skills but also enhances their personal growth, helping them to cultivate a sense of identity and purpose. Transforming hobbies into university subjects represents a progressive shift in educational philosophy, emphasizing the importance of passion in learning and the relevance of personal interests in academic achievement and professional development. It encourages universities to adapt their programs to meet the evolving needs and desires of students, ultimately creating a more enriching and fulfilling educational experience.